Menstrual Health: Family Support and Household Practices among Bachelor Level Female Students - Upadhya (Adhikari), Shanta (KMC Journal, 2025)
Menstrual health is an important part of women’s well-being, and family support plays a key role during menstruation. This study aims to identify the situation of family support and household practices. A quantitative research approach with descriptive method was employed to survey 340 out of 2,294 randomly selected female students at Surkhet Multiple Campus. The findings highlight that families play a crucial role in helping ease menstrual discomfort by showing empathy, providing practical support and maintaining open communication. In that time, providing nutritious food, ensuring access to sanitary products and offering emotional support can significantly enhance the quality of life during menstruation. The study also revealed that traditional and cultural practices still influence household behavior towards menstruation. Ninety-four percent of respondents reported being restricted from activities such as attending religious ceremonies, entering prayer rooms and visiting temples. Additionally, sixty-nine percent of respondents faced restrictions from cooking food during their periods. Furthermore, eighty-two percent of respondents mentioned that menstruation is often viewed through the lens of social and cultural traditions, requiring them to follow customs like avoiding physical contact with men and staying out of the kitchen during menstruation. These findings underline the continued influence of cultural beliefs on menstrual practices and highlight the importance of education and family support to promote a more positive and supportive environment during menstruation.